Implantación de contabilidad comercial y análisis financiero en el tecnicentro rojas la experiencia a su servicio de la ciudad de Loja, provincia de Loja. Periodo mayo – junio 2016 - Guzmán Costa, Bertha Yolanda (2016)
This research work is called “IMPLEMENTATION OF COMMERCIAL AND FINANCIAL ANALYSIS ACCOUNTING IN RED Tecnicentro EXPERIENCE AT YOUR SERVICE CITY OF LOJA, LOJA.PERIODO PROVINCE MAY-JUNE 2016; which it aimed to provide a tool for control of resources available to the company and improve its efficient development and development of the company. The overall objective was to implement the Commercial Accounting and Financial Analysis Tecnicentro ROJAS EXPERIENCE AT YOUR SERVICE of the city of Loja , for decision -making. The methodology used for the development of the research was to apply the source documents such as purchase invoices and sales to be ordered for the accounting process the same that was initiated with the initial inventory, then a chart of accounts was developed, the state initial situation, daybook, ledger, trial balance and finally the income statements were presented, plus financial indicators where the economic reality of the company is reflected were applied. Upon completion of the research work is concluded by the accounting process that allows real results on the financial situation of the company, it is recommended to apply the accounting system cone a tool to help improve the profitability of the entity.